The Relation between Economic Development and Business Ownership revisited - Martin Carree; André van Stel; Roy Thurik; Sander Wennekers (Tinbergen Institute, 2007)
This paper revisits the two-equation model of Carree, van Stel, Thurik and Wennekers (2002) where deviations from the `equilibrium' rate of business ownership play a central role determining both the growth of business ownership and that of economic development. Two extensions of the original setup are addressed: using longer time series of averaged data of 23 OECD countries (up to 2004) we can discriminate between different functional forms of the `equilibrium' rate and we allow for different penalties for being above or under the `equilibrium' rate. The additional data do not provide evidence of a superior statistical fit of a U-shaped `equilibrium' relationship when compared to an L-shaped one. There appears to be a growth penalty for having too few business owners but not so for having too many.
Keywords: L26; O10; 330; entrepreneurship; economic development; economic growth; business ownership; Eigentümerstruktur; Wirtschaftswachstum; Empirische Methode; OECD-Staaten